Membangun Budaya Membaca Melalui Gerakan Literasi Jakarta Book Party - Nurhasanah, Nabilah Putri; Anwar, Rully Khairul; Rohman, Asep Saiful (Pustabiblia: Journal of Library and Information Science, 2025)
Reading is a culture that must be developed in the current era to improve the quality of human resources. Information literacy is also an important skill that individuals have to be able to access information correctly, solve problems, and play an active role in social life.  This research aims to find out the role of the Jakarta Book Party literacy movement in b[1]uilding and improving the reading culture of the community. This research was conducted using a qualitative method with participant observation data collection. The results of this study show that the literacy movement with the Jakarta Book Party program is considered successful in encouraging community involvement in literacy activities even though there are obstacles in its activities such as the lack of clarity in providing information about the detailed location, so that participants have difficulty in finding the location point. However, this literacy movement made participants actively involved in its activities such as interaction and exchange of ideas. Overall, the program was effective in building a reading culture and has the potential to develop further with the right strategy.